2019
DOI: 10.3390/md17040194
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cholesterol, Glycemia Control and Short- and Long-Term Antihypertensive Effects of Smooth Hound Viscera Peptides in High-Salt and Fructose Diet-Fed Wistar Rats

Abstract: In this study, the antihypertensive activity of Purafect®-smooth hound viscera protein hydrolysate (VPH) and its peptide fraction with molecular weight (MW) below 1 kDa (VPH-I) was investigated. In addition, the lipase inhibitory activity, as well the anticoagulant potential, in vitro, were assessed. The antihypertensive effects of VPH and VPH-I were studied during 24 h (short-term effect) and 30 days (long-term effect) using high-salt (18% NaCl) and -fructose (10%) diet (HSFD)-induced hypertension. Data showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…In the present study, high-fructose/high-salt intake caused a state of metabolic syndrome as evidenced by hyperinsulinemia, weight gain, dyslipidemia and hyperuricemia as was previously reported [22]. There was also a strong correlation between IR and body weight gain, while both AM6545 and AM4113 decreased body weight in IR animals but with lost IR/body weight correlation.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, high-fructose/high-salt intake caused a state of metabolic syndrome as evidenced by hyperinsulinemia, weight gain, dyslipidemia and hyperuricemia as was previously reported [22]. There was also a strong correlation between IR and body weight gain, while both AM6545 and AM4113 decreased body weight in IR animals but with lost IR/body weight correlation.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, it is necessary to take renal function parameters into account to analyze this disease. The serum levels of UA and BUN reflect the filtration rate of the glomerular . In our study, rats’ renal function is impaired after consuming a high fructose and salt diet for 8 weeks, which is evidenced by abnormal renal index, UA, BUN, CREA levels, and renal pathological changes in HFSD-fed rats.…”
Section: Discussionmentioning
confidence: 51%
“…The serum levels of UA and BUN reflect the filtration rate of the glomerular. 37 In our study, rats' renal function is impaired after consuming a high fructose and salt diet for 8 weeks, which is evidenced by abnormal renal index, UA, BUN, CREA levels, and renal pathological changes in HFSD-fed rats. However, the renal index, BUN level, and pathological changes are normalized after being supplemented with coriander, elucidating coriander is able to alleviate HFSD-caused renal impairment.…”
Section: ■ Discussionmentioning
confidence: 58%
“…Both of them reduced the adipose tissue weight in rats [76]. Some authors [77] have demonstrated that the visceral proteolysis of starfish reduces TC and TG levels and improves lipid metabolism in HFD rats. Another research show that hydrolysates of Octopus vulgaris muscles proteins decreases the levels of TG, TC and LDL-C in hyperglycemia rats induced by alloxan, improves the lipid metabolism as well as reverses the increase in the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase and gamma-glutamyl transpeptidase caused by alloxan, playing a certain role in liver protection [78].…”
Section: Proteins and Bioactive Peptidesmentioning
confidence: 97%